The year of the genome : a diary of the biological revolution - Weissmann, Gerald (Henry Holt, 2003)
"For over a year, beginning in early 2000, the celebrated essayist and research physician Gerald Weissmann carefully documented the modern age of enlightenment in biology, charting its scientific marvels and new plagues. In this illuminating journal, he takes us on a literary exploration of laboratories and beyond to see the impact on human life and culture of such headline-making developments as RU 486, AIDS drugs, stem cells, and the decoding of the human genome."